Perencanaan Kesejahteraan Hari Tua pada Warga Kelurahan Semolowaru Kecamatan Sukolilo Surabaya - Ani Suhartatik; C. Erna Susilawati; Arini Arini; Ninuk Muljani; Tuty Lindawati; P. Julius F. Nagel; Shanti Shanti (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2021)
This Abdimas activity aims to provide insight to the residents of Semolowaru Village, Sukolilo District, Surabaya on the importance of financial management for retirement planning. The target of this activity is 40 residents of Semolowaru Village who are members of Pemberdayaan dan Kesejahteraan Keluarga (PKK) Rukun Warga 03, Semolowaru Village, Surabaya. The implementation of this Abdimas activity uses discourse, discussion, practice, and simulation to prepare a family revenue and expense budget. The members of PKK Rukun Warga 03, Semolowaru Village, Surabaya are given the opportunity to practice their abilities, for example completing tasks and exercises in financial planning for the welfare of pension time, checking the financial health of the family with the Financial Health Check-up website program.